دراسة لنموذج كيدا للتنبؤ بالفشل المالي للشركات بالتطبيق على شركات المساهمة في بورصة عمان - حواس, عبد الرزاق; مجدوب, علاء الدين (جامعة الوادي - University of Eloued, 2021)
إن موضوع الفشل المالي للمؤسسات الاقتصادية من المواضيع المهمة التي شـغلت العديـد مـن الهيئات والمنظمات الدولية، لما له من آثار سلبية على مـستوى الـمؤسسة ومحيطها من متعاملين وشركاء ومهتمين، كما أن عملية التنبؤ بالفشل المالي يساعد في اتخاذ القرارات في المؤسسة من أجل التخفيف من هاته الاثار وتمكينها من تحقيق فرض الاستمرارية، وتعتبر النسب المالية الركيزة الأساسية في هذه العملية من خلال إيجاد النسب التي تساهم في تفسير الفشل المالي، وتشكيل أو اقتراح نماذج من خلالها تكشف مسبقا عن احتمال وقوعه، ومن هذا المنطلق هدفت هذه الدراسة إلى قياس مدى فاعلية نموذج كيدا(Kida Model) الخاص بالتنبؤ بالفشل المالي على الشركات المدرجة على بورصة عمان، ولقد تم تطبيق هذه النموذج على 15 شركة فاشلة تم إحالتها للتصفية أو شركات متوقفة و15 شركات مستمرة غير محالة للتصفية (سليمة) ولقد توصلت الدراسة إلى أن نموذج كيدا (Kida Model) كان يميل إلى التنبؤ بالفشل المالي، وأنه يمكن الاعتماد عليه في الحكم على الوضع المالي للشركات بدرجة ثقة مقبولة بلغت نسبة 66.67% خلال ثلاث سنوات. الكلمات المفتاحية: الفشل المالي، التنبؤ بالفشل المالي، النسب المالية، نموذج كيدا. The issue of financial failure of economic institutions is one of the important issues that have occupied many international bodies and organizations, because of its negative effects on the level of the institution and its surroundings of dealers, partners and interested, also the process of predicting financial failure helps in making decisions in the institution in order to mitigate these effects and enable them to achieve the imposition of continuity, and the financial ratios are the main pillar in this process by finding ratios that contribute to the interpretation of financial failure, and form or propose models through which they reveal in advance the possibility of its occurrence. This study aimed to measure the effectiveness of the Kida Model for predicting financial failure on the listed companies on the ASE. The study indicated that the Kida Model tended to predict financial failure, and that it could be relied upon to judge the financial position of companies with an acceptable confidence level of 66.67% within three years. Keywords: financial failure, financial failure prediction, financial ratios, Kida Model.
Study the Kida model for predicting financial failure for companies by applying to joint stock companies at the Amman Stock Exchange
Keywords: الفشل المالي، التنبؤ بالفشل المالي، النسب المالية، نموذج كيدا